QUALITY CONTROL OF DIGITAL MAMMOGRAPHY EQUIPMENT AT KING CHULALONGKORN MEMORIAL HOSPITAL - THEERAKUL, Kanlayanee; KRISANACHINDA, Anchali (The ASEAN Journal of Radiology, 2023)
Mammography equipment has been used to display Thai women's breast image for more than 30 years. The quality control of the equipment performed by technologists was started no longer than 5 years. The program covers the darkroom cleanliness, processor quality control and mammographic phantom imaging. The quality control tests performed by medical physicist is firstly responsible by the government inspector from Department of Medical Sciences, Ministry of Public Health. The visit is upon requested annually to verify the system performance prior to certification. Very few tests had been conducted according to the limited number in human resources, knowledge and test tools. Digital Spot Mammography system was firstly installed in 1995, follow by the Digital Full-Field Mammography System in 1999 at King Chulalongkorn Memorial Hospital. The quality control program followed the manufacture guideline for MQSA and Non-MQSA Facilities was started after the system installation. Two parts from the QC program are prepared for technologists and medical physicists. The first part was performed and the data from June 2002-2003 was collected, analyzed and presented in this report. The objective of this study is to stress the important of image quality, the safety standards, economical criteria of film retake rate as well as the patient dose reduction. The result shows that most data are in the acceptable limit. The system is well maintained by the service engineer under the service contract. The program for medical physicist covers the system performance study, the hardware assessment such as the collimation, the monitor, viewing facilities, the radiation dose measurement and the overall image quality parameters. More test tool and radiation detector are required for the second part. Furthermore, the test should be performed and evaluated by the experienced medical physicist in this field to fulfill the objective.